Examining University Leadership Preparation: An Analysis of Program Attributes and Practices. (December 2018) - Anderson, Erin; Winn, Kathleen M.; Young, Michelle D.; Groth, Cori; Korach, Susan; Pounder, Diana; Rorrer, Andrea K.
This study uses data from the Initiative for Systemic Program Improvement through Research in Educational Leadership ( INSPIRE ) Preparation Program Features Survey to respond to national critiques of university-based principal preparation programs. The findings provide insight into the program content and relevancy, personnel, and content delivery of 97 principal preparation programs affiliated with the University Council for Educational Administration (UCEA). We found that UCEA institutions align their curriculum and assessment designs to national standards, actively engage in formalized partnerships with districts, engage their candidates in a variety of assessment practices for formative and summative purposes, and work to offer coursework that bridges classroom assignments to field-based experiences.